Income Inequality: Socio-Economic Challenges of the 21st Century and Efforts to Overcome Them - Riyadi, Muhammad (Journal of Economic Growth and Development Review, 2024)
Income inequality has become one of the most significant socio-economic challenges of the 21st century. This research examines global inequality trends, analyzes the causal factors, and evaluates efforts to overcome them. Using data from a variety of trusted sources, the study finds a consistent increase in global income inequality since the 1980s, with the Gini ratio increasing from 0.61 to 0.67. Factors such as globalization, automation, and economic policies contribute to this trend. The impact of inequality extends to various aspects, including social mobility, community cohesion and economic growth. Although some policy interventions have shown positive results, their implementation faces significant challenges. This research concludes that a multidimensional and collaborative approach is needed to effectively address income inequality. Recommendations include integrated policy reform, increased investment in education and social protection, and stronger international cooperation. This study emphasizes the urgency of coordinated action to build a fairer society and a sustainable economy in the global era.